Retratos do cotidiano: as mulheres do assentamento rural Santa Vitória - Souza, Janete Monteiro de (2002)
The present work shows trajectories of life of seated women agricultural, with the objective to apprehend on aspects to the experience of its sexuality. The daily one of the seated woman is constructed in a new space, called agricultural nesting whose formation if presents with proper singularity to a social and economic context and politician of the Great River of the North. Its passages of life are permeaty by different violences suffered in its daily one and its sexuality is weaveeed by a set of rules that the naturalization of the subordination of the woman in relation to the man keeps. The societies use the systems of the relations between men and women and transform the biological characteristic into activities human beings